PENGARUH FAKTOR PRODUKSI TERHADAP PENDAPATAN PEMETIK DAUN KAYU PUTIH - Hendro Prahasto (Jurnal Penelitian Hasil Hutan, 1988)
Leaf  cutting  activity  gave contribution to  the  total  income  of  cajuput  leaf cutters  with  an average of  Rp.162,000 per year  or approximately  41%  of  the  total  income.   The result  of  linear regression  analysis shows  that  the  income  from cajuput leaf  cutting  gave a significant   income  contribution  to the  leaf  cutters  total  income.Based  on the  result  of  Cobb-Douglas analysis, it is shown that  four  production  variables  i.e. share  area  (Xl), work time  spent outside   the  leaf  cutting activity  (X2), work time spent   for  leaf  cutting activity (X3), and  capital  or farming   production  cost (X4) gave a  significant   impact   on  the  total  income   of  leaf  cutters.   The  production  function: equation isIn Y = 3.5385+0.1189 In XI + 0.0283 In X2 + 0.2976 In X3 + 0.1255 In X4 + E with  determination coefficient   (R2)  of  0.7549.